Recovery And Tamper Localization For Reversible Iris Image Watermarking Scheme Using Hash Function - Muhammad Alif Aiman, Abd Samad (2023)
Digital watermarking is a technique for embedding identifying information, such as a logo or text, into a digital media file, such as an image, audio, or video. The watermark is usually subtle and may be invisible to the naked eye, but it can be used to identify the owner or creator of the content, or to track its distribution. Digital watermarking can be used for a variety of purposes, including copyright protection, content identification, and tracking the distribution of digital media. Tamper and counterfeits are quite common especially when it comes to the digital image. The tamper of the digital image can affect the security aspect in which it authenticates the image that has been tampered as legitimate which can cause damage or data stolen. That is why, it is important to protect intellectual property and ensuring that digital content is used appropriately. Thus, this paper will propose the method that can be applied to enhance the digital images to prevent any counterfeit and improve the security.